Correction: Applications of Raman spectroscopy in the development of cell therapies: state of the art and future perspectives. Issue 7 (4th March 2020) - Rangan, Shreyas; Schulze, H. Georg; Vardaki, Martha Z.; Blades, Michael W.; Piret, James M.; Turner, Robin F. B.
Abstract : Correction for 'Applications of Raman spectroscopy in the development of cell therapies: state of the art and future perspectives' by Shreyas Rangan et al., Analyst, 2020, DOI: 10.1039/c9an01811e.